Introducing voluntary agencies in India - Sen, A. C. (Ed.) (New Delhi, 1990)
Introducing Voluntary Agencies in India is a modest attempt to present at one place a brief record of the aims, activities and organisation of 41 leading voluntary agencies in the country which are members of the Association of Voluntary Agencies for Rural Development (AVARD). Together, they represent nearly two fifths of AVARD's total member ship. But their scope and range of activities cover almost the entire gamut of voluntary action which the challenging task of rural development has evoked in this country panchayati raj, sarvodaya, cooperation, intensive area development, research and teaching, extension and training.
Keywords: Voluntarism